Local spring effect in titanium-based layered oxides. Issue 11 (21st October 2020) - Su, Heng; Guo, Gencai; Ren, Yang; Yu, Xiqian; Zhang, Xu; Ma, Tianyuan; Lu, Yue; Zhang, Zihe; Ma, Hao; Sui, Manling; Li, Hong; Sun, Chengjun; et al.
Abstract : The local spring effect in titanium-based layered oxides can release stress well during the cycling process and enhance the battery cycle performance. Abstract : Titanium-based layered oxides (TLOs) are one of the most promising electrode material families for sodium-ion batteries (NIBs) due to their smooth charge/discharge profiles and excellent cycle performance. However, the reaction mechanism of these materials, especially the reason for the disappearance of multiple voltage plateaus, is still not clear. Herein, two representative TLOs (Na2/3 Ni1/3 Ti2/3 O2 and Na2/3 Co1/3 Ti2/3 O2 ) with the same P2 crystal structure have been studied to scrutinize those unexplained issues. In situ synchrotron high-energy X-ray diffraction revealed a solid solution reaction mechanism for both, suggesting the absence of rigid phase transitions upon electrochemical cycling. An interesting "spring effect" of the TiO6 octahedron, i.e., the reversible vibration of the central Ti atom inside the local octahedron upon electrochemical redox, was demonstrated by advanced X-ray absorption spectroscopy and theoretical calculations. Such an effect could suppress the rigid phase transitions, and result in smooth charge/discharge profiles and enhanced cycle stability. This work not only accounts for the disappearance of multiple voltage plateaus of TLOs for NIBs, but also provides an effective local-structure viewpoint to increase the cycle stability of electrode materials for other advanced battery systems.